The Adjustment of Peak Ground Acceleration Value Based on Modification of Attenuation Constant with Accelerograph Data from 2020-2023 in Bali Region - Mayumi Cahyandari; Winardi Tjahyo Baskoro; I Putu Dedy Pratama; I Made Yuliara; Hery Suyanto; I Gde Antha Kasmawan (Buletin Fisika)
This study aims to determine the empirical formula model of maximum ground acceleration (PGA) in the Bali region by modifying the attenuation constant based on accelerograph data from 2020-2023 obtained from the BMKG Class II Sanglah Geophysical Station. The data used consists of 443 accelerograph recordings from 146 earthquake events, with a coverage area of ??113.51 ° - 115.83 ° E and 12.56 ° - 7.71 ° S. Through linear regression analysis, the empirical PGA model for the Bali region is obtained: log10 PGA = (-1.817) log10 (R) + (0.809) M - 0.089. This model is also compared with the attenuation model from Donovan, Setiawan, and Lin and Wu, with the results showing that the developed model has a very strong correlation of 0.782 between the PGA from observations and the PGA from the model which is included in the very strong category. In addition, the MSE value of 0.209 and RMSE of 0.457 from this model indicate that the model has a good level of accuracy in predicting PGA values. These findings provide a significant contribution in improving seismic risk prediction in the Bali region, which can be used as a basis for more effective disaster mitigation planning.